Anlotinib combined with anti-PD-1 antibody, camrelizumab for advanced NSCLCs after multiple lines treatment: An open-label, dose escalation and expansion study. (October 2021) - Zhou, Na; Jiang, Man; Li, Tianjun; Zhu, Jingjuan; Liu, Kewei; Hou, Helei; Zhang, Xiaochun
Highlights: Anlotinib plus camrelizumab showed efficacy and manageable toxicity for NSCLCs. 12 mg Anlotinib could be the MTD of combination therapy. Brain metastasis and ECOG could be risk factors for the combination therapy. Abstract: Objectives: Combined therapy should be invested for those patients who are refractory to first-line therapy. Anti-angiogenic agents could enhance tumor immunity response. We designed a phase IB clinical trial and analyzed the effectiveness and safety of anlotinib combined with PD-1inhibitors Camrelizumab for multi-line pretreated and failed advanced NSCLC to explore the synergistic effect of anti-angiogenic agents and immunotherapy. Methods: All enrolled patients should receive camrelizumab 200 mg every 3 weeks. Eligible patients were randomized successively to three dose cohorts of Anlotinib in a dose escalation clinical setting. Once maximal tolerable dose was established, the primary end point of this study was progression-free survival, overall survival and safety. Risk factor was an exploratory end point. Results: The identified expansion dose for anlotinib was 12 mg. The median PFS of ITT patients was 8.2 months (95% CI, 4.3–12.1 months). And the mOS was 12.7 months (95% CI, 10.2–15.1 months). There was significant difference of mPFS between the 8 mg cohort and the 12 mg cohort (5.6 m vs.11.0 m, p = 0.04). Patients with brain metastasis had a significantly higher risk of death (HR 5.90; 95% CI 2.01–17.30; P = 0.001). Patients whose ECOG was 0 and 1 had a significantly lower risk of death (HR 0.36; 95% CI 0.14–0.91; P = 0.031). Conclusions: Anlotinib plus camrelizumab had shown promising efficacy and manageable toxicity as a second-line or later-line treatment for NSCLCs, especially in the 12 mg cohorts. Large-scale phase III clinical trials are needed to further explore the rational combination models and biomarkers.